2022
DOI: 10.1039/d2ta04912k
|View full text |Cite
|
Sign up to set email alerts
|

Practical conversion-type titanium telluride anodes for high-capacity long-lifespan rechargeable aqueous zinc batteries

Abstract: Rechargeable aqueous zinc batteries (RAZBs) with high safety and low cost offer great hopes for complementing lithium-ion batteries. However, realizing practical high-safety and long-lifespan RAZBs is held back by the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The Nyquist plots of the heterostructured FeSe 2 /MoS 2 and the FeSe 2 /MoS 2 Mixture cathodes are depicted in Figure a to explore the reaction kinetics. The value of the electrochemical impedance depends on the interfacial charge/ion transfer process and the properties of the SEI layer. , The corresponding equivalent circuit diagram is shown in Figure S2. It is observed that the heterostructured FeSe 2 /MoS 2 cathode delivers a smaller resistance ( R ct = 60 Ω) than that of the FeSe 2 /MoS 2 mixture cathode ( R ct = 114 Ω), verifying the high charge/ion conductivity and stable interfacial contact between electrode and electrolyte. , The fast reaction kinetics of the heterostructured FeSe 2 /MoS 2 could be attributed to its strong charge-redistribution capability provided by the built-in electric field as shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nyquist plots of the heterostructured FeSe 2 /MoS 2 and the FeSe 2 /MoS 2 Mixture cathodes are depicted in Figure a to explore the reaction kinetics. The value of the electrochemical impedance depends on the interfacial charge/ion transfer process and the properties of the SEI layer. , The corresponding equivalent circuit diagram is shown in Figure S2. It is observed that the heterostructured FeSe 2 /MoS 2 cathode delivers a smaller resistance ( R ct = 60 Ω) than that of the FeSe 2 /MoS 2 mixture cathode ( R ct = 114 Ω), verifying the high charge/ion conductivity and stable interfacial contact between electrode and electrolyte. , The fast reaction kinetics of the heterostructured FeSe 2 /MoS 2 could be attributed to its strong charge-redistribution capability provided by the built-in electric field as shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…The value of the electrochemical impedance depends on the interfacial charge/ion transfer process and the properties of the SEI layer. 47,48 The corresponding equivalent circuit diagram is shown in Figure S2. It is observed that the heterostructured FeSe 2 /MoS 2 cathode delivers a smaller resistance (R ct = 60 Ω) than that of the FeSe 2 / MoS 2 mixture cathode (R ct = 114 Ω), verifying the high charge/ ion conductivity and stable interfacial contact between electrode and electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…The smaller R ct (2.3 Ω) of S–MoS 2 than that of MoS 2 (2.4 Ω) illustrates the enhanced conductivity and faster charge-transfer process. 38,39 Moreover, the ion-diffusion capacity of S–MoS 2 and MoS 2 were qualitatively measured according to formulas (1) and (2): 40,41 Z ′ = R ct + R e + σω −1/2 where R and T are the gas constant and temperature, respectively. A and n refer to the cathode area and number of electrons transferred during the reaction, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between the peak current ( i ) and scan rate ( v ) in CV curves is based on formula (1). 44 i = av b where both a and b are adjustable parameters. The definite b -value is obtained by fitting the linear relationship between log( i ) and log( v ).…”
Section: Resultsmentioning
confidence: 99%